High performance computing : ISC High Performance 2016 International Workshops, ExaComm, E-MuCoCoS, HPC-IODC, IXPUG, IWOPH, P 3MA, VHPC, WOPSSS, Frankfurt, Germany, June 19-23, 2016, Revised selected papers /: ISC High Performance 2016 International Workshops, ExaComm, E-MuCoCoS, HPC-IODC, IXPUG, IWOPH, P 3MA, VHPC, WOPSSS, Frankfurt, Germany, June 19-23, 2016, Revised selected papers. (2016) - Unknown
No abstract available